L’art beauvoirien de (re)vivre la mutilation sous le diktat de l’Histoire et du temps - Ledwina, Anna (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Simone de Beauvoir’s texts show the acute presence of history in the writer’s life,and the futility of individual human actions, a sense of meaningless life, which contrastswith the author’s optimistic vision of the world. For this reason, the human being feels lostand crippled, especially a woman for whom the reality of war means alienation, anxiety,inability to fulfill the dream of unity with another person. This approach allows the author,who is an existentialist, to pay special attention to gender antagonism and social rolesassigned to the eternally (dominant) man and (subordinate) woman. Beauvoir’s writingbecomes the cry of an individual forced to face his own helplessness, failure and tragedyof the world. Struggling with loneliness, the feminine characters, disappointed, subject tothe dictates of time, live only in the present, bereft of the past and future, by the fault ofthe Other. However, despite being aware of failure they fight against adversity in searchfor a better life.